PENGARUH SAMPAH ORGANIK TERHADAP KARAKTERISTIK KIMIA VERMIKOMPOS - Ahmad Ilham Tanzil; Puji Rahayu; Raudhotun Jamila; Wahyu Indra Duwi Fanata; Ummi Sholikhah; Tri Ratnasari (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Vermicompost is a fertilizer produced by composting organic matter by utilizing the interaction between earthworms and microorganism. Vermicompost also contains a number of macro and micro nutrients needed by plants. Besides containing macro and micro of nutrients, vermicompost also containing growth hormone such as cytokinins and auxins which are produced by worms during the composting process. The benefits of vermicompost are that it can improve the physical, chemical and biological properties of soil, increase the ability of the soil to retain water, rebuild damaged soil structures and increase ability of the soil to exchange cations. The fermentation process lasted for 14 days using Lumbricus rubellus worms. The choice of this type worm is based on its character which has a high level of productivity, can eat all types of organic matter, is much more adaptive and move less actively. This research was held in Sumbersalak Village, Ledokombo District, Jember Regency and also involving the Kenconowungu farmer group. Goat manure become waste in this village so it has potential to be developed further as the main ingredient for vermicompost. The other additional materials such as vegetable and fruits waste, and leaf litter were used as factor (treatment). These three types of materials are used to find out which treatment gives the best vermicompost quality. Chemical analysis was carried out in this study to determine the organic N, P, K, C organic, pH, and water content. The result of the analysis will be compared with the standards of Minister of Agriculture No.70 of 2011.